Model Kolaborasi Karakteristik Budaya Organisasi Sharing Dalam Perilaku Birokrat Di Masa Pandemi (Studi Kasus Desa-Desa Kecamatan Banjaran Kabupaten Bandung) - Mulyaningsih; Ieke Sartika Iriany (Jurnal Dialektika: Jurnal Ilmu Sosial, 2023)
Abstract The COVID-19pandemic has spawned many types of policies to implement; (WFH), implementation of social distancing, and, physical distancing, (PSBB), Implementation of Community Activity Restrictions (PPKM), PPKM, and even Area Closure. The increase in cases is less controlled and the handling is not optimal due to unresponsiveness, lack of sense of crisis, slow government response, weak bureaucratic structure, not adaptive to health problems, coordination between stakeholders, central and regional governments, and citizens' indifference to health protocols. This study uses a combination of descriptive and quantitative data with SPSS 2003 from the survey results as many as 61 officers and residents randomly from 11 villages in Banjaran District, Bandung Regency. The results of the study present a collaborative model of sharing organizational culture characteristics in bureaucratic behavior from 17 factors with 31 indicators that can reduce the rate of positive cases of COVID -19 by 57.8% so that it is more optimal to increase the competitiveness, identity of officers through improving social media technology (IT) capabilities. ) with the millennial community through financial sharing so that cross-community togetherness grows. Role models for bureaucrats in serving the people in general, this research can be carried out more broadly nationally, in Asia and even the world. The identity of the apparatus through increasing the ability of social media technology (IT) with the millennial community through financial sharing so that cross-community togetherness grows. Role models for bureaucrats in serving the people in general, this research can be carried out more broadly nationally, in Asia and even the world. The identity of the apparatus through increasing the ability of social media technology (IT) with the millennial community through financial sharing so that cross-community togetherness grows. Role models for bureaucrats in serving the people in general, this research can be carried out more broadly nationally, in Asia and even the world. Keywords: Pandemic, Collaboration Model, Sharing Organizational Culture, Bureaucratic Behavior, Role Model Abstrak Pandemi COVID-19melahirkan banyak jenis kebijakan untuk dijalankan; (WFH), penerapan social distancing, dan, physcial distancing, (PSBB), Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM), PPKM berlevel bahkan Penutupan Wilayah. Peningkatan kasus kurang terkendali dan tidak optimalnya penanganan disebabkan ketidaktanggapan, kurang sense of crisis,lambannya respons pemerintah, lemahnya struktur birokrasi,tidak adaptif pada masalah kesehatan, koordinasi antar stakeholder, pemerintah pusat maupun daerah serta ketidakpedulian warga terhadap protokol kesehatan. Penelitian ini menggunakan kombinasi metode (mixed methods) deskriftif dan data kuantittif dengan SPSS 2003 dari hasil survey sebanyak 61 responden aparat dan warga secara random dari 11 Desa se Kecamatan Banjaran Kabupataen Bandung. Hasil penelitian menyajikan sebuah model kolaborasi karakteristik budaya organisasi sharing dalam perilaku birokrat dari 17 faktor dengan 31 indikator dapat menurunkan tingkat kasus positif COVID -19 sebanyak 57,8% agar lebih optimal perlu meningkatkan daya saing, jati diri aparat melalui peningkatan kemampuan teknologi medsos (IT) dengan komunitas melinial melalui financial sharing sehingga tumbuh kebersamaan lintas komunitas. Role model bagi pelaku birokrat dalam melayani rakyat pada umumnya, penelitian ini dapat dilakukan lebih luas secara Nasional,Asia bahkan Dunia. Kata Kunci: Pandemi, Model Kolaborasi, Budaya Organisasi Sharing, Perilaku Birokrat, Role Model